Transparent Peace Fines for Economic Crimes Policy - Wijayanti, Suci; Suparji, Suparji; Suwadi , Pujiyono (Lembaga Contrarius Indonesia, 2025)
The peace fine mechanism has increasingly been applied as an alternative to formal judicial proceedings in resolving economic crimes in Indonesia. However, its growing use reveals significant juridical and conceptual problems, particularly the lack of an integrated legal framework and the fragmentation of regulation across sectoral laws. These conditions generate legal uncertainty and raise concerns regarding accountability and the potential abuse of discretionary power by law enforcement authorities. This study aims to examine the normative foundation, scope, and limitations of the peace fine mechanism by focusing on the boundaries of prosecutorial authority and the implications for the principle of legality. To achieve this objective, the research applies a normative legal method with a doctrinal approach, systematically analyzing statutory instruments, including the Economic Crime Law, the Prosecutor’s Law, the Anti-Corruption Law, and relevant sectoral regulations. This study produces three principal findings. First, existing sectoral legislation implicitly recognizes non-judicial settlement mechanisms; however, the Indonesian legal system does not provide a comprehensive regulatory framework that clearly delineates the criteria, procedures, and legal consequences of the peace fine mechanism. Second, the absence of such regulation generates legal uncertainty and enables large corporations to circumvent criminal liability. Third, based on these findings, the study affirms the urgent necessity for the State to formulate and enact a comprehensive Economic Criminal Law to guarantee legal certainty, accountability, and coherence in the application of both judicial and non-judicial settlement mechanisms for economic crimes